A Review on Fungal Infections and Their Treatments in Children with Renal Disorders - Nateghian, Alireza (Journal of Pediatric Nephrology, 2017)
Fungal infections especially invasive ones (IFI), now are among well known and hard to manage problems in various kidney diseases in children. Various databases including pubmed, scopus, ovid and Web of Science Core Collection were looked for keywords including antifungals, fungal infections, kidney diseases Since 1990 to 2017. Renal side effects were looked using the site WWW.DRUG.COM as well. For common cases with Identified Pathogens Infectious diseases society of America (IDSA) recommendations for antifungal therapy as the most acceptable plan has been summarized at the end of article; specific therapeutic issues have been also discussed in their sections. Keywords: Fungal Infections; Renal Diseases; Acute Kidney Injury; Hemodialysis; CAPD, Kidney Transplantation.